The great imitator - Cristina Gozzi; Maurizio Tognetti; Lucio Brugioni (Italian Journal of Medicine, 2014)
B.K. a Moroccan 32-year-old man was admitted to our hospital for abdominal pain and vomiting. He showed an increase of inflammation indexes, abdominal free fluid, axillary, inguinal and abdominal lymphadenitis, pleural effusion, ascites and thickened intestinal walls. The patient also presented alopecia and facial erythema, a positive anti-nuclear antibodies (ANA) test (1:1280). Lastly the diagnosis of systemic lupus erythematosus (SLE) was made. The patient was treated with high doses of corticosteroid; abdominal pain decreased and pleural effusion and ascites disappeared. After several days he started to complain of significant chest pain. He had a troponin increased above 100 ng/mL, modified electrocardiogram, pericardial effusion and edema of ventricular walls as in myocarditis. The patient was treated successfully with cyclophosphamide and pericardial effusion and chest pain disappeared. After 1 month at the hospital the patient was discharged and referred to a rheumatologist for the follow up. Systemic lupus erythematosus is an autoimmune disease in which autoantibodies and immune-complexes damage heart, joints, skin, blood vessels, liver, kidneys and the nervous system. Ninety percent of individual diagnosed with SLE are women. The course is unpredictable with periods of acute illness alternating with periods of remission. This is a typical disease that requires a differential diagnosis, because the symptoms may vary widely and are unpredictable. According to the American College of Rheumatology, which drew up a reference list of 11 symptoms, SLE is confirmed when 4 out of the 11 symptoms are present simultaneously or symptoms overlap on two separate occasions. Treatment can include corticosteroids and antimalarial drugs, intravenous immunoglobulins and cytotoxic drugs such as cyclophosphamide. Our case is exceptional because it is rare for a young man to be affected. He had 5 out of 11 symptoms: malar rash, serositis, arthritis, hematologic disorder and ANA test positive.